Valorization of mulberry (Rubus glaucus) by-products: ultrasound-assisted extraction of total anthocyanins - Ordóñez-Santos, Luis Eduardo; Esparza-Estrada, Jessica; Osorio Mora, Oswaldo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
In this study, the objective was to establish parameters of optimization of the factors such as solvent concentration, extraction time and liquid-to-solid ratio in ultrasound-assisted extraction (UAE) of total anthocyanins from mulberry by-products. The study sample corresponds to mature fruits that did not comply with the size demanded by the market (by-product). Three independent variables including extraction time (6-74 min), liquid-solid ratio (33-66.16 mL/g), and ethanol concentration (63-96%) were investigated. A rotatable central composite design (CCD) and response surface methodology (RSM) was used to investigate the effect of process variables. The optimum conditions of ultrasound-assisted extraction obtained through response surface methodology were as follow: extraction time, 20 min; liquid to solid ratio, 60:1 mL/g, and ethanol concentration, 90%, allowed to obtain a maximum concentration of 259.66 mg/L. To validate the optimized model, the experimental values were compared with the predicted values to check the adequacy of the model. Ultrasound extraction was 13.60% higher than maceration technique and reduces the time from 24h to 20 minutes. The results show that ultrasonic-assisted extraction as a promising agro-industrial process in the recovery of anthocyanins from mulberry by-products.